2016
DOI: 10.1007/s10461-016-1545-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ARV Associated Adverse Drug Reactions in Influencing Adherence Among HIV-Infected Individuals: A Systematic Review and Qualitative Meta-Synthesis

Abstract: Poor adherence remains a major barrier to achieving the clinical and public health benefits of antiretroviral drugs (ARVs). A systematic review and qualitative meta-synthesis was conduct to evaluate how ARV adverse drug reactions may influence ARV adherence. Thirty-nine articles were identified, and 33 reported that ARV adverse drug reactions decreased adherence and six studies found no influence. Visually noticeable adverse drug reactions and psychological adverse reactions were reported as more likely to cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 60 publications
(100 reference statements)
2
37
0
Order By: Relevance
“…While adverse drug reactions (ADRs), treatment tolerability, clinic attendance, development of coinfections, concomitant treatments, and treatment/pill fatigue have been identified as barriers to adherence, cumulative time on treatment has also been associated with decreases in adherence levels. 5 , 6 , 9 , 24 26 It is at this time, later on in treatment, where a simplified, single-pill per day regimen may be more effective than a multi-pill regimen (each with varying dosing instructions serving to increase patient burden). Conversely, a FDC may be restrictive in its ability to form part of a holistic treatment plan which addresses coinfections.…”
Section: Discussionmentioning
confidence: 99%
“…While adverse drug reactions (ADRs), treatment tolerability, clinic attendance, development of coinfections, concomitant treatments, and treatment/pill fatigue have been identified as barriers to adherence, cumulative time on treatment has also been associated with decreases in adherence levels. 5 , 6 , 9 , 24 26 It is at this time, later on in treatment, where a simplified, single-pill per day regimen may be more effective than a multi-pill regimen (each with varying dosing instructions serving to increase patient burden). Conversely, a FDC may be restrictive in its ability to form part of a holistic treatment plan which addresses coinfections.…”
Section: Discussionmentioning
confidence: 99%
“…Pinheiro et al 13 found that elderly patients had a higher adherence rate and, consequently, that a higher proportion of these patients had an undetectable viral load. Additionally, nonadherence has been correlated with use of illicit drugs, 14,15 smoking, 14,16 alcohol consumption, 16 depressive symptoms, 17 lower schooling levels and economic status, 8,15 adverse reactions, 18 symptoms of opportunistic diseases 8 and longer time between infection and receiving the diagnosis of HIV and starting treatment. 15 Interruption or irregularity of use of antiretroviral drugs is a public health problem in the fight against the HIV epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…HAART usage is associated with development of adverse oral complications, resulting from oral and perioral manifestations due to oral ulcerations, epithelial hyperplasia and xerostomia [24,25], that damage the mucosal epithelium and potentially expose the underlying tissues to infections due to multiple microorganisms, including HPV infections [24][25][26]. Damage-induced inflammation in the oral epithelium decrease patient adherence to drug regimens [51], that ultimately correlate with suboptimal drug levels and development of drug resistance that could compromise future therapy. Patients on HAART may develop painful oral lesions that affect chewing and swallowing, further contributing to development of malnutrition and weight loss, and also adds to the increased morbidity [52].…”
Section: Discussionmentioning
confidence: 99%